ANALISIS PENGARUH RISIKO BANK TERHADAP PROFITABILITAS BANK SYARIAH PERIODE 2020-2023 - Krisma Sri Pamungkas Lindung Prakoso; Muhammad Sholahudin (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of Bank risk on the profitability of Islamic Banks for the period 2020-2023. This research method uses a quantitative approach. The data collection method in this study uses the documentation method. The population used is all Islamic banks listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 period with a total of 33 companies. The sampling technique in this study used probability sampling.  The data used in this study are secondary data. The data source used is through the analysis of the financial statements of all companies that are the research sample with a period range of 2020-2023. The data analysis technique in this study used panel data regression analysis. The results of this study are that simultaneously all NPF, CAR, and BOPO variables can have a significant effect on ROA at Islamic banks in 2020-2023. Partially, the NPF and CAR variables do not have a significant effect on ROA growth at Islamic Banks in 2020-2023. Partially, the BOPO variable can have a significant negative effect on ROA growth at Islamic Banks in 2020-2023.